The HopF family of Pseudomonas syringae type III secreted effectors. (9th June 2016) - Lo, Timothy; Koulena, Noushin; Seto, Derek; Guttman, David S.; Desveaux, Darrell
Summary: Pseudomonas syringae is a bacterial phytopathogen that utilizes the type III secretion system to inject effector proteins into plant host cells. Pseudomonas syringae can infect a wide range of plant hosts, including agronomically important crops such as tomatoes and beans. The ability of P. syringae to infect such numerous hosts is caused, in part, by the diversity of effectors employed by this phytopathogen. Over 60 different effector families exist in P. syringae ; one such family is HopF, which contains over 100 distinct alleles. Despite this diversity, research has focused on only two members of this family: HopF1 from P. syringae pathovar phaseolicola 1449B and HopF2 from P. syringae pathovar tomato DC3000. In this study, we review the research on HopF family members, including their host targets and molecular mechanisms of immunity suppression, and their enzymatic function. We also provide a phylogenetic analysis of this expanding effector family which provides a basis for a proposed nomenclature to guide future research. The extensive genetic diversity that exists within the HopF family presents a great opportunity to study how functional diversification on an effector family contributes to host specialization.